Extrachromosomal Nucleolus-Like Compartmentalization by a Plasmid-Borne Ribosomal RNA Operon and Its Role in Nucleoid Compaction - Mata Martin, Carmen; Sun, Zhe; Zhou, Yan Ning; Jin, Ding Jun (Frontiers in Microbiology, 2018)
Escherichia coli RNA polymerase (RNAP) molecules are concentrated and form foci at clusters of ribosomal RNA (rRNA) operons resembling eukaryotic nucleolus in fast-growing cells. The bacterial nucleolus-like organization, spatially compartmentalized at the surface of the compact bacterial chromosome (nucleoid), serves as transcription factories for rRNA synthesis and ribosome biogenesis, which influences the organization of the nucleoid. Unlike wild type that has seven rRNA operons in the genome in a mutant that has six (6rrn) rRNA operons deleted in the genome, there are no apparent transcription foci and the nucleoid becomes uncompacted, indicating that formation of RNAP foci requires multiple copies of rRNA operons clustered in space and is critical for nucleoid compaction. It has not been determined, however, whether a multicopy plasmid-borne rRNA operon (prrnB) could substitute the multiple chromosomal rRNA operons for the organization of the bacterial nucleolus-like structure in the mutants of 6rrn and 7rrn that has all seven rRNA operons deleted in the genome. We hypothesized that extrachromosomal nucleolus-like structures are similarly organized and functional in trans from prrnB in these mutants. In this report, using multicolor images of three dimensional superresolution Structured Illumination Microscopy (3D-SIM), we determined the distributions of both RNAP and NusB that are a transcription factor involved in rRNA synthesis and ribosome biogenesis, prrnB clustering, and nucleoid structure in these two mutants in response to environmental cues. Our results found that the extrachromosomal nucleolus-like organization tends to be spatially located at the poles of the mutant cells. In addition, formation of RNAP foci at the extrachromosomal nucleolus-like structure condenses the nucleoid, supporting the idea that active transcription at the nucleolus-like organization is a driving force in nucleoid compaction.